2019
DOI: 10.1021/acs.biomac.9b00433
|View full text |Cite
|
Sign up to set email alerts
|

Highly Ordered Gelatin Methacryloyl Hydrogel Foams with Tunable Pore Size

Abstract: In this study, we present a fast and convenient liquid foam templating route to generate gelatin methacryloyl (GM) foams. Microfluidic bubbling was used to generate monodisperse liquid foams with bubble sizes ranging from 220 to 390 μm. The continuous phase contained 20 wt % GM and 0.7 wt % lithium phenyl-2,4,6-trimethylbenzoylphosphinate as photoinitiator. Gelation was achieved via UV-initiated radical cross-linking of GM. After cross-linking, the hydrogel foams were either swollen in water or freeze-dried. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 54 publications
0
36
0
Order By: Relevance
“…However, the control of architectural parameters including the pore size distribution, the porosity, and the interconnection size remain challenging, thus, the geometry of these scaffolds is rather random as shown in Figure 1 e. Conversely, a precise control of the pore size within the micrometric range can be reached through physical foaming and especially by microfluidics. In that case, bubbles are generated one by one in a chip and packed in a container where the bubble assembly forms an initially liquid foam which becomes solid after polymerization [ 45 , 46 , 47 ]. One advantage of this individualized bubble formation is that the resulting foams have a narrow pore size distribution, therefore the final scaffolds are highly homogenous and reproducible.…”
Section: Overview Of the Techniques Used For Fabrication Of Porousmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the control of architectural parameters including the pore size distribution, the porosity, and the interconnection size remain challenging, thus, the geometry of these scaffolds is rather random as shown in Figure 1 e. Conversely, a precise control of the pore size within the micrometric range can be reached through physical foaming and especially by microfluidics. In that case, bubbles are generated one by one in a chip and packed in a container where the bubble assembly forms an initially liquid foam which becomes solid after polymerization [ 45 , 46 , 47 ]. One advantage of this individualized bubble formation is that the resulting foams have a narrow pore size distribution, therefore the final scaffolds are highly homogenous and reproducible.…”
Section: Overview Of the Techniques Used For Fabrication Of Porousmentioning
confidence: 99%
“…Costantini et al [ 51 , 52 ] confirmed that alginate scaffolds generated by microfluidics with monodisperse pore size distribution have an improved interconnectivity, and consequently, a better nutrient supply to cells compared to scaffolds prepared by chemical foaming. Furthermore, Dehli et al [ 45 ] generated a gelatin methacryloyl hydrogel-based foam using microfluidics bubbling to produce a macroporous and ordered hydrogel as a promising candidate as a scaffold for tissue engineering. Nevertheless, microfluidics bubbling is still at the early stages of development and many aspects need to be addressed in order to broaden its applications.…”
Section: Overview Of the Techniques Used For Fabrication Of Porousmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan and aliginate are both biocompatible, and thus their foams have potential tissue engineering applications. Solidfication of the liquid foam template involves heating [111], freeze-drying [113,114], and/or cross-linking [103] through the presence of photoinitiators, as in the case of gelatin methacryloyl (GM) foams [115], where generated liquid foams from microfluidic bubbling is exposed to UV light. Recent developments have also employed valve-based microfluidic flow-focusing (vFF), where the orifice size is controlled in real time during the passage of two immiscible fluids, thereby allowing immediate variation of bubble sizes [106].…”
Section: Formation Of Solid Foam Structuresmentioning
confidence: 99%
“…10,16 For foam templating, on the other hand, liquid foams are used as structuring templates for the synthesis of solid foams. Typically, aqueous solutions of (bio-) polymers such as chitosan [17][18][19][20][21][22] or (modied) gelatin [23][24][25][26][27][28] that contain a surfactant and a crosslinking agent are used for this templating route. In the rst step, the aqueous solution is foamed via bubbling, stirring, or microuidics.…”
Section: Introductionmentioning
confidence: 99%